The study of Interacting Partners of a Transcription Factor, YB-1 - Mansor, Mohamad Hafizi (2005)
The transcription factor, YB-1 was considered to be a transcription factor. YB-1 also involved in many genes regulation, such as genes involved in cell proliferation and cell growth, DNA repair, multi drug resistance, modification of chromatin, redoxstate dependent-transcriptional enhancing, tissue cell specific processes, stress response, immune response (major histocompatibility class II genes), and many more. Because of several important of YB-1, my supervisor proposed to study of YB- 1 's interacting partners. Base on interacting partner of YB-1, we hopefully can explore properties of YB-1. In this study, we used culture ofHeLa cells, and lysis the cells using Single-step lysis for extraction of total cellular protein, and nuclear and cytoplasmic proteinextraction methods to get YB-1 protein. Using co-immunoprecipitation analysis and several antibodies, we will detect interacting partners of YB-1. Finally after co-immunoprecipitation analysis, we got YB-1 protein has specific interaction with P-glycoprotein mdr 1 protein which involved in multidrugresistant cancer cells.